Wittgenstein and Critical Theory: Mickaëlle Provost in Conversation with Alice Crary - Crary, Alice; Provost, Mickaëlle (Nordic Wittgenstein Review, 2022)
This is the second of two parts of an interview with Alice Crary conducted in a single exchange in the first weeks of January 2022, where she discusses ordinary language philosophy and feminism, Wittgenstein’s conception of mind and its relation to feminist ethics, the link between Wittgenstein and Critical Theory, and her own views about efforts to bring about social and political transformations. The first part on “Wittgenstein and Feminism” is published in the NWR Special Issue “Wittgenstein and Feminism”, forthcoming later this year.